2009
DOI: 10.1039/b807497f
|View full text |Cite
|
Sign up to set email alerts
|

Predicting skin permeability using liposome electrokinetic chromatography

Abstract: The potential of liposome electrokinetic chromatography (LEKC), which is applied to estimate compound penetration through the skin, was evaluated in this report. Quantitative retention-activity relationships (QRARs) were successfully constructed between the compound skin permeability coefficient (log K(p)) and the retention values (log k), as well as some calculated molecular descriptors by the stepwise regression method (R(2) = 0.902). Furthermore, the developed vector method was applied to compare the simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Recently, it was demonstrated that LEKC is a promising method to predict drug penetration through the skin. Quantitative retention-permeability relationships (QRPeRs) were successfully constructed between skin permeability coefficients (log K p ) and retention values (log k) (118).…”
Section: Liposome Electrokinetic Chromatography (Lekc)mentioning
confidence: 99%
“…Recently, it was demonstrated that LEKC is a promising method to predict drug penetration through the skin. Quantitative retention-permeability relationships (QRPeRs) were successfully constructed between skin permeability coefficients (log K p ) and retention values (log k) (118).…”
Section: Liposome Electrokinetic Chromatography (Lekc)mentioning
confidence: 99%
“…The systems include the immobilized artificial membrane (Barbato et al, 1998), biopartitioning micellar chromatography (Escuder-Gilabert et al, 2003;Waters et al, 2013), liposome electrokinetic chromatography (Wang et al, 2009), and keratin immobilized on the silica as a stationary phase (Turowski and Kaliszan, 1997). However, in respect to the optimization of the formulation destined for the administration onto the skin, the effects of various additives and carriers/vehicles on the drug penetration, these chromatographic systems exhibit a very limited potential and are therefore not further discussed in this review.…”
Section: Artificial In Vitro Skin Modelsmentioning
confidence: 99%
“…Measurements and computations indicated that a good linear correlation can established between the retention behavior of the analytes and their skin permeation capacity. The method was proposed for the prediction of drug permeation through the skin (Wang et al, 2009a;Wang et al, 2009b).…”
Section: Liposome Electrokinetic Capillary Chromatographymentioning
confidence: 99%